2005
DOI: 10.1074/jbc.m500304200
|View full text |Cite
|
Sign up to set email alerts
|

Proliferating Cell Nuclear Antigen (PCNA) May Function as a Double Homotrimer Complex in the Mammalian Cell

Abstract: The diverse function of proliferating cell nuclear antigen (PCNA) may be regulated by interactions with different protein partners. Interestingly, the binding sites for all known PCNA-associating proteins are on the outer surface or the C termini ("front") sides of the PCNA trimer. Using cell extracts and purified human PCNA protein, we show here that two PCNA homotrimers form a back-to-back doublet. Mutation analysis suggests that the Arg-5 and Lys-110 residues on the PCNA back side are the contact points of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
69
1
6

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(85 citation statements)
references
References 34 publications
9
69
1
6
Order By: Relevance
“…44,45 Additionally, PCNA was previously detected as dimer and trimer on 2D SDS-PAGE 42 and, more recently, double trimeric structure was described. 31,32 Our findings therefore agree with those reported in the literature.…”
Section: Pcna Isoforms Expression In Hccsupporting
confidence: 93%
See 1 more Smart Citation
“…44,45 Additionally, PCNA was previously detected as dimer and trimer on 2D SDS-PAGE 42 and, more recently, double trimeric structure was described. 31,32 Our findings therefore agree with those reported in the literature.…”
Section: Pcna Isoforms Expression In Hccsupporting
confidence: 93%
“…[24][25][26][27][28][29] Other than forming a homotrimeric structure, PCNA also has been found to form double homotrimeric complexes. [30][31][32] As each monomer has specific protein binding sites, the polymeric structure allows PCNA to bind different partners suggesting that the aggregation status may be relevant for its functions.…”
mentioning
confidence: 99%
“…Proliferating cell nuclear antigen (PCNA) is central for many essential cellular processes such as DNA replication and damage repair, transcription, chromosome segregation, and cell-cycle progression [1][2][3][4][5][6][7][8]. All of these functions are carried out by PCNA in the nucleus.…”
Section: Introductionmentioning
confidence: 99%
“…Data obtained by several different techniques demonstrated that PCNA molecules form a single or double homotrimer complex that encircles the DNA fiber, and functions as a sliding clamp for DNA polymerases and a docking station for many protein partners [3,[10][11][12][13][14][15]. A PCNA ring may bind to different protein partners at different time and space to carry out specific tasks [3,5,16,17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation